Fire and Fury : Inside the Trump White House - Wolff, Michael 1953- (New York, New York : Henry Holt and Company, 2018)
Thanks to his deep access to the West Wing, Michael Wolff tells the story of the stormy first nine months of Donald Trump's term as President.
Keywords: Trump, Donald, -- 1946-; Presidents -- United States; United States -- Politics and government -- 2017-